Dopamine and glucose sensors based on glassy carbon electrodes modified with melanic polymers - González, Rosa (2004)
This work deals with the study of polymers electrogenerated from different catechols at glassy carbon electrodes and the analytical applications of the resulting modified electrodes for dopamine quantification and glucose biosensing. The electropolymerization was performed from a 3.0 × 10 -3 M catechol solution (catechol, dopamine, norepinephrine, epinephrine or L-dopa in a 0.050 M phosphate buffer pH 7.40) by applying 1.00 V for 60 min. The properties of the polymers are very dependent on the nature of the catechol, L-dopa being the best. Glassy carbon electrodes modified with melanic polymers electrogenerated from L-dopa and norepinephrine were found to be suitable for dopamine determinations in flow systems, although the behavior was highly dependent on the nature of the monomer. Detection limits of 5.0 nM dopamine and interferences of 9.0 and 2.6% for 5.0 × 10-4 M ascorbic acid and 5.0 × 10-5 M dopac, respectively, were obtained at the glassy carbon electrode modified with a melanin-type polymer generated from L-dopa (using 1.0 × 10-3 M AA in the measurement solution). The advantages of using a melanin-type polymer generated from dopamine to improve the selectivity of glucose biosensors based on carbon paste electrodes containing Pt and glucose oxidase (GOx) are also discussed. The resulting bioelectrodes combines the high sensitivity of metallized electrodes with the selectivity given by the polymeric layer. They exhibit excellent performance for glucose with a rapid response (around 10 seconds per sample), a wide linear range (up to 2.5 × 10-2 M glucose), low detection limits (143 μM) and a highly reproducible response (R.S.D of 4.9%). The bioelectrodes are highly stable and almost free from the interference of large excess of easily oxidizable compounds found in biological fluids, such as ascorbic acid (AA), uric acid (UA) and acetaminophen.